Medicinal plants used by various ethnic groups in Sarawak - Fasihuddin, B.A.; B. Din, Laily (Malaysian Journal of Science, 2017)
Fifty medicinal plants used by various ethnic groups in Sarawak were collected and their uses have been recorded. This report is part of an on-going ethnobotanical survey carried out in Borneo.